The Perinatal Loss Care Educational Programme and Its Evaluation - Ratislavová Kateřina; Štípková Martina (Sciendo, 2019)
Working with bereaved parents is an immense challenge for professionals in the field of perinatal care and requires a high level of knowledge and skill. This article aims to evaluate the effectiveness of the Perinatal Loss Care blended educational programme.